1990
DOI: 10.1126/science.2218503
|View full text |Cite
|
Sign up to set email alerts
|

Extrageniculate Vision in Hemianopic Humans: Saccade Inhibition by Signals in the Blind Field

Abstract: The functional competence of extrageniculate visual pathways in hemianopic humans was demonstrated by showing that distractor signals in the blind half of the visual field could inhibit saccades toward targets in the intact visual field. This inhibitory effect of unseen distractors in patients occurred only when distractors were presented in the temporal half of the visual field, was specific to oculomotor responses, and did not occur in normal subjects. These results show that a peripheral visual signal activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(107 citation statements)
references
References 25 publications
7
94
6
Order By: Relevance
“…Selective activation from LSF stimuli is consistent with anatomical evidence that these brain areas receive substantial magnocellular inputs [9,42,61], possibly as part of a phylogenetically old route specialised for the rapid processing of fear-related stimuli [21,41,50,56,59].…”
Section: Introductionsupporting
confidence: 56%
“…Selective activation from LSF stimuli is consistent with anatomical evidence that these brain areas receive substantial magnocellular inputs [9,42,61], possibly as part of a phylogenetically old route specialised for the rapid processing of fear-related stimuli [21,41,50,56,59].…”
Section: Introductionsupporting
confidence: 56%
“…The use of accuracy as a potentially more sensitive measurement than RT has previously been noted by many authors. For instance, Santee and Egeth (1982) suggested that under the Bdata-limited^conditions (Norman & Bobrow, 1975) of briefly presented displays, accuracy measures are more sensitive to perceptual processes (see also Gellatly, Cole, Fox, & Johnson, 2003;Milliken & Tipper 1998;Rafal, Smith, Krantz, Cohen, & Brennan, 1990;Skarratt, Gellatly, Cole, Pilling, & Hulleman, 2014). Empirical support for this has come from Cole, Kuhn, Heywood, and Kentridge (2009), who showed that although color Bsingletons^do not automatically attract attention when RT is used to index capture, they do so when a Bone-shotĉ hange detection method is used.…”
Section: Methodsmentioning
confidence: 91%
“…On the basis ofvon Skramlik's findings, we would say, in the terms we have adopted, that human subjects are tetrageusic for his salt stimuli. Since forced-choice procedures were not used, however, von Skramlik's work cannot be regarded as conclusive by today's psychophysical standards (for a discussion offorced-choice efficacy, see Rafal, Smith, Krantz, Cohen, & Brennen, 1990). Nonetheless, his work suggests that the total number of neural signals encoding gustatory stimuli is small.…”
Section: Methodology In Taste-discrimination Experimentsmentioning
confidence: 99%